The differences of e-shopper typology in online buying satisfaction among UPM's students, Serdang - Osman, Syuhaily; Then, Sook Han; Jamaluddin, Askiah (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The purpose of this study is to determine the differences of e-shopper typologies in online buying satisfaction among students in Universiti Putra Malaysia. A systematic random sampling procedure was used to select 150 respondents. A self-administered questionnaire was used as a tool for data collection. The result showed that most of the respondents were grouped as convenience shoppers which indicated that engagement in online shopping was based upon online convenience motive. On the whole, a large proportion of respondents were categorized into the cluster of moderately satisfied towards their online buying experience. One-way analysis of Variance was used to examine the significant differences of four groups of e-shopper in terms of online buying satisfaction. Clusters of e-shopper were found to have significant differences in terms of online buying satisfaction (F = 3.210, p ≤ 0.05). The LSD post hoc test found that mean were different between convenience shoppers and balanced buyers which indicated that convenience shoppers were more satisfied towards their online buying experience than balanced buyers. Findings from this study are beneficial to both e-retailers and consumers as it helps retailers to develop a better understanding of e-shopper and enhance consumers’ self-understanding as an e-shopper.